Normalizing Industrial Policy - Rodrik, Dani (World Bank, Washington, DC, 2017)
The theoretical case for industrial policy is a strong one. The market failures that industrial policies target in markets for credit, labor, products, and knowledge have long been at the core of what development economists study. The conventional case against industrial policy rests on practical difficulties with its implementation. Even though the issues could in principle be settled by empirical evidence, the evidence to date remains uninformative. Moreover, the conceptual difficulties involved in statistical inference in this area are so great that it is hard to see how statistical evidence could ever yield a convincing verdict. A review of industrial policy in three non-Asian settings El Salvador, Uruguay, and South Africa highlights the extensive amount of industrial policy that is already being carried out and frames the need for industrial policy in the specific circumstances of individual countries. The traditional informational and bureaucratic constraints on the exercise of industrial policy are not givens; they can be molded and rendered less binding through appropriate institutional design. Three key design attributes that industrial policy must possess are embeddedness, carrots-and-sticks, and accountability.